The Impact of Authentic Leadership on Innovative Work Behavior: Mediating Roles of Proactive Personality and Employee Engagement - Bai, Yina; Wang, Zheng; Alam, Mehboob; Gul, Fozia; Wang, Yiqun (Frontiers in Psychology, 2022)
The purpose of the study is to investigate the impact of authentic leadership and proactive personality on innovative work behavior through dual mediation approach. This study applied a judgment sampling technique and data were gathered from 311 high-tech manufacturing industries of Shenzhen, China. The measurement model and structural model were tested using structural equation modeling technique through AMOS 24 software. The results indicate that authentic leadership has a positive and significant effect on proactive personality. Meanwhile, findings show that proactive personality has a significant impact on innovative work behavior. Moreover, findings show that proactive personality positively mediates the relationship between authentic leadership and innovative work behavior. Furthermore, findings illustrate that work engagement positively mediates the relationship between proactive personality and innovative work behavior. This study provides insightful and valuable implications to high-tech manufacturing industries executives and regulators interested in organizational productivity.